(untitled) (Global Journal of Science Frontier Research, 2022)
This paper is an overview of imaging methods used for research and diagnosis that appear in the literature There are several types of scientific research and imaging modalities including photography microscopy ultrasound Xray computed tomography CT magnetic resonance imaging MRI and positron emission tomography PET The type of images used will depend on the part of the body the researcher wants to see in the image and the types of images readily available to the patient For many years medical imaging has played an important role in the early detection diagnosis and treatment of cancer and other diseases In some cases medical imaging tests are the first step in preventing the spread of cancer by detecting it early and in many cases the cancer can be cured or eliminated CT scans MRIs ultrasounds and X-ray imaging are very important tools in fighting various diseases Medical imaging is also used to create accurate computer models of body systems organs tissues and cells used in anatomy and physiology classes in medical school